Do parents know best? The short and long-run effects of attending the schools that parents prefer - Diether W. Beuermann; Clement Jackson (Inter-American Development Bank (IDB), 2018)
Recent studies document that, in many cases, the schools that parents prefer over others do not improve student test scores. This could be because (a) parents cannot discern schools causal impacts, and/or (b) parents value schools that improve outcomes not well-measured by test scores. To shed light on this, we employ administrative and survey data from Barbados. Using discrete choice models, we document that most parents have strong preferences for the same schools. Using a regression-discontinuity design, we estimate the causal impact of attending a preferred school on a broad array of outcomes. As found in other settings, more preferred schools have better peers, but do not improve short-run test scores. However, for females, these schools confer long-run benefits including reduced teen pregnancy, more educational attainment, increased employment, higher earnings, and improved health. In contrast, for males, the effects are mixed. The pattern for females is consistent with parents valuing school impacts on outcomes not well-measured by test scores, while the pattern for males is consistent with parents being unable to identify schools' causal impacts.
Keywords: I20; J0; 330; Barbados; peer quality; school preferences